Community Perspectives On Employing Herbal Plants Betel Leaves, in Hypertension - Sumara, Retno; Sumarliyah, Eni; Puspa Miralda, Rindiani (Indonesian Academia Health Sciences Journal, 2024)
Background : Treatment for hypertension sufferers is not only medical but can also use natural ingredients in the form of standardized herbs and herbal therapy. This encourages hypertension sufferers to try traditional treatment. In fact, there are still many people who do not know about existing herbal treatments. This is because people are not exposed to information. It was found that this wrong perception arose due to a lack of good communication from authorities such as health workers to convince the public about the effectiveness of herbal plant management. Objective: This study aims to determine the people’s perception of the use of betel leaf plants in hypertensive patients in East Kalianget Village. Method: This research uses a descriptive method. The total population was 196 respondents. The sampling technique used was purposive sampling. With a sample of 131 respondents suffering from hypertension. The data collection technique is in the form of a questionnaire. Data processing uses the SPSS program with Descriptive Analysis. Results: This research shows that as many as 107 people (81.7) have positive perceptions about the use of betel leaf plants in East Kalianget Village, Sumenep. In conclusion, there is a positive public perception that supports the application of betel leaf plants by individuals suffering from hypertension. Both medical and non-medical approaches can be used to treat and prevent hypertension. It is said that using traditional medicine—especially using betel leaves—is safer than using modern treatment.